Designing an Automated Badminton Shuttlecock Launcher to Enhance the Athletic Performance of Badminton Players - Afif Rusdiawan; Titis Yutno Isain; Muhammad Syariffuddien Zuhrie; Muhammad Labib Siena Ar Rasyid (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research aims to develop an automatic shuttlecock throwing/launcher device and reveal the suitability of this device for badminton experts and athletes. This research is research and development (R&D) research. The flow of development research carried out is 1) potential problems, 2) problem analysis, 3) initial product, 4) expert validation and revision, 5) small-scale trials and revisions, 6) large-scale trials and revisions, and 7) final product. Three experts assessed this tool, including media experts, badminton coaches, and sports experts (academics). The research subjects used in the small-scale trial stage were badminton athletes from the PB Pratama Surabaya club with 12 athletes. In comparison, 41 athletes from 4 different clubs were used in the large-scale trial stage. The research results show that this shuttlecock launcher was declared feasible from expert validation after revision, small-scale trials, and large-scale trials. From the three stages of research, a feasibility percentage value of more than 80% was obtained, so it can be concluded that the shuttlecock launcher developed has good feasibility. The conclusion is that this badminton shuttlecock throwing device with a remote control as a controller that coaches can use has been declared feasible and ready for mass production. So, it will impact increasing the efficiency and effectiveness of the coaches' performance in developing the abilities of badminton athletes.